An empirical investigation of the portuguese housing prices: evidence from the period 2004-2018 - Jianmin Luo (2019)
Housing market is an essential segment of the whole country’s economy. Recently, the rising house prices in Portugal reflects a booming economy. This article presents an integrated macro view of the Portuguese housing market with macroeconomic indicators. Firstly, it compares the housing market and several macroeconomic indicators from 2004 to 2018. Then, the dynamic analysis of the housing prices by different regions in Portugal and its typology included. Also, the article is complemented with the regression analysis to identify the relationship between the house prices and macroeconomic indicators. Several macroeconomic indicators are incorporated, such as GDP, unemployment rate, shortterm interest rates, inflation, personal income, investments, immigration, and housing stock. Results show GDP and the housing prices might have a positive correlation. The unemployment rate might affect the income and continue its impact on consumer behaviour. The level of immigration and foreign investments continue to grow indebted. The current negative interest rates are increasing the demand for houses and the housing prices. The housing stock in Portugal is mostly fixed but may experience limited growth as the rebuild program and new constructions. The housing prices in the Algarve and Lisbon are markedly more expensive than the interior. The demand for the different type of houses tended to focus on personal’s need during the recession period. From the regression analysis, the unemployment rate is the closest correlated variable among them. Overall, the housing prices are currently growing and the housing economy and macroeconomic closely related each other.